Effect of irrigation water of the main out full with addiation Gypsum Phosphate on growth of barley ( Hordeum Vulgare ) - A. hasoon, Elham; S.Al – kinany, Fadhel; R.J. Al–Jeboory, Sabbar; H.Al–hadithy, Azzam (Journal of Kerbala for Agricultural Sciences, 2017)
Two experiments was conducted. The first experiment is laboratory, by using the Columns techniques to evaluate the effectiveness of Gypsum Phosphate as a chemical mending. The second experiment is a biological to evaluate the efficiency of Gypsum Phosphate to improve the qualities of the soil cultivated flora of barley which irrigated by the saline water of the main out full at Abu-Ghariab location. 0,50 and 100 ton . ha-1 of Gypsum Phosphate was added at two replicate then irrigated water given at 5000 m3. ha-1. Results of chemical analysis tests of the soil columns (colums technique) showed and proved using Gypsum Phosphate efficiency as good chemical mending at saline water as important calcium resource, as well as Gypsum Phosphate addition in columns technique leads to reduce EC and SAR in soil to a limit value which allowed for optimal growth of barley plants, also leads to reduce absorption of Sodium Na+ by plants roots and thus improve the most nutrient absorption, which reflected positively in increasing plant growth. Also increasing of Calcium concentration in columns Cause led to the removal of agreater amount of sodium out of the roots zone and thus improving the qualities of soil chemical,physical and fertility. Results also indicate that the optimal level of Gypsum Phosphate addition was at level 50 ton.ha-1. And the higher level of it was unsignificant economically.